SISTEM PELELANGAN IKAN KOI BERBASIS WEBSITE - Ika Menarianti; Debri Kamanda Gunawan; Sudargo (Lembaga Pengembangan Kinerja Dosen, 2023)
The lack of optimal koi auction results and the lack of participants in koi auction activities are thea main reasons for creating this system. Fish auctions that are less than optimal can even resukt in big losses. The auction system is made so that the result of selling fish are maximized. Waterfall was chosen to build an auction system to facilitate the fish aucyion process and also to increase the interest of bidders because this system is easy to use on all platform. This system has been tested through the black box test which states all the system functions run well and efficiently. External and internal validators also agreed to use the system by 89,87% and 94%. The practicality of the system was also agreed by respondents ay 86,07%.